Blockchain technology system on student academic performance in higher education as perceived by students in Portugal - Mata, M. N.; Haider, S. A.; Dantas, R. M.; Rita, J. X.; Lucas, J. L. (Studies in Higher Education, 2025)
This study conceptually identified the most influential factors from previous studies, which were extracted and classified into contexts based on the technology acceptance model and expectation confirmation theory framework. The purpose of this study is to examine the impact of blockchain system perceived quality and perceived usability on student academic performance (SAP) through the mediating role of student satisfaction and the moderating role of continuance intention. The convenience sampling technique was used to collect data from 583 students studying in different private and public universities in Portugal. Hypotheses were tested using partial least squares-structural equation modeling (PLS-SEM) with SmartPLS software version 4. The findings revealed that the direct effect of blockchain system perceived quality on SAP is positive and significant, while perceived usability is not significant. Moreover, student satisfaction positively and significantly mediates the relationship between perceived quality and SAP, as well as between perceived usability and SAP. Lastly, continuance intention as a moderator has a positive and significant influence on student satisfaction and SAP. The relationship between blockchain system perceived quality, perceived usability on SAP represents a novel contribution through the mediation of student satisfaction and the moderation of continuance intention between student satisfaction and SAP.